Untangling blockchain technology: A survey on state of the art, security threats, privacy services, applications and future research directions. (March 2021) - Bhushan, Bharat; Sinha, Preeti; Sagayam, K. Martin; J, Andrew
Highlights: Presents an in-depth survey of blockchain and its underlying technologies. Investigates the data privacy requirements and redefines the data privacy concept in blockchain. Presents a systematic survey on the blockchain security threats along with their attack vectors, cause and the proposed countermeasures. Identifies the critical open challenges that restricts the practicality of blockchain and provides a roadmap of encouraging research avenues for which future research is required. Abstract: Blockchain is a distributed, decentralized public ledger that has gained massive momentum recently. Currently, security services such as privacy, confidentiality, resource provenance, access control, authentication and integrity assurance are managed by centralized controllers. However, this centralization faces numerous security and privacy challenges. Blockchain solve such challenges as it helps to create an attack resistant, digital data storage as well as sharing platform by employing linked block structures for data verification and trusted consensus mechanism for data synchronization. The goals of this paper are to provide an in-depth survey of blockchain technology, to provide insights into the blockchain security threats, to highlight the privacy necessities for current applications, to outline their challenges and give an insight on how these challenges can be resolved by the blockchain technology. Furthermore, we summarize the future research challenges associated with the usage of blockchain based security services to spur further investigation in this field. Graphical abstract: Image, graphical abstract